2017
DOI: 10.1021/acs.jpclett.7b02622
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Electron Injection and Defects at the TiO2/CH3NH3PbI3 Interface of Perovskite Solar Cells

Abstract: We investigated electron injection rates and vacancy defect properties by performing first-principles calculations on the interface of an anatase-TiO(001) and a tetragonal CHNHPbI(110) (MAPbI(110)). We found that the coupling matrix element between the lowest unoccupied molecular orbital of MAPbI and the TiO conduction band (CB) minimum is negligibly small, the indication being that electron-injection times for low-energy excited states are quite long (more than several tens of picoseconds). We also found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 79 publications
2
21
1
Order By: Relevance
“…Furthermore, the charge transport layers in devices are usually mixed with the GRMs, which further complicates computational modeling. Ab initio calculations have been used to probe interfaces between GRMs/TiO 2 , MAPbI 3 /TiO 2 , and as discussed in this review MAPbI 3 /GRMs. However, a realistic description of the ternary interfaces between perovskites and mixed charge transport layers remains currently particularly demanding.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the charge transport layers in devices are usually mixed with the GRMs, which further complicates computational modeling. Ab initio calculations have been used to probe interfaces between GRMs/TiO 2 , MAPbI 3 /TiO 2 , and as discussed in this review MAPbI 3 /GRMs. However, a realistic description of the ternary interfaces between perovskites and mixed charge transport layers remains currently particularly demanding.…”
Section: Discussionmentioning
confidence: 99%
“…One major reason is the conduction band of TiO 2 is lower than that of the halide perovskite such as MAPbI 3 and MASnI 3 (MA = CH 3 NH 3 , methylammonium) [16,17]. Therefore, first-principles computational studies of TiO 2 /perovskite interfaces have been an emerging topic recently [16][17][18][19][20][21][22][23][24].…”
Section: Tio 2 /Perovskite Interfacementioning
confidence: 99%
“…The defect properties at the TiO 2 /perovskite interface were also studied from first-principles calculations. In 2017, Haruyama et al reported the defect properties at the a TiO 2 (101)/tMAPbI 3 (110) interface using first-principles computational approach, in which anatase TiO 2 (001) was placed on the MAPbI 3 (110) plane [20]. They found that the vacancy defects in the TiO 2 layer create undesired defect levels within the bandgap, which serves as hole traps and recombination centers; while most of the vacancy defects in the MAPbI 3 layer produces no additional states, thus having no influence on the electron-hole separation rates.…”
Section: Tio 2 /Perovskite Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, transition metal substituents in the TiO 2 layer are quite important and further characterizations are required to understand the effects of substituents in the CH 3 NH 3 PbI 3 /TiO 2 interface. Although the electronic properties of perovskite/ETL interface have been widely investigated by experiments and density-functional-theory (DFT) calculations [24,25,26,27,28,29,30,31], the existence of theoretical studies aiming to understand the fundamental role of the interfacial substituents is still rather scarce. In addition to the primary experiments, the first-principles DFT calculations are highly important to acquire further knowledge concerning the effects of transition metal substitution and contribute to new strategies for interface optimization.…”
Section: Introductionmentioning
confidence: 99%